A whitening repair composition containing a dual nano delivery system and a preparation method thereof

CN122973303APending Publication Date: 2026-10-27GUANGZHOU QINGNANG BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611297874.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

本发明通过设计特定比例的神经酰胺组合物与脂质类成分组合,并结合三段控温长周期相诱导工艺,制备获得了含高比例长周期相的多层囊泡,其能够与角质层脂质膜融合递送,帮助难溶且难渗透的EO型神经酰胺经皮渗透。将该纳米囊泡与负载光甘草定的载体复配,获得的组合物在光甘草定稳定性、经皮渗透、美白和屏障修复方面均表现出显著的协同增效作用。因此,本发明的组合物可应用于治疗屏障受损和色素沉着等复合性肌肤问题,在化妆品领域具有良好的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a whitening and repairing composition containing a double-nanometer delivery system and a preparation method thereof, and belongs to the field of cosmetics. The composition comprises a first nanometer delivery system and a second nanometer delivery system. The first nanometer delivery system comprises glabridin and a carrier material loaded with the glabridin. The second nanometer delivery system comprises a ceramide composition and a lipid component. The second nanometer delivery system has a multilamellar vesicle structure with a high long-period phase ratio, can fuse with a stratum corneum lipid membrane for delivery, and helps to penetrate the EO type ceramide which is difficult to dissolve and penetrate through the skin. The nanometer vesicle is compounded with the first nanometer delivery system loaded with the glabridin, and the obtained composition shows a significant synergistic effect in terms of glabridin stability, transdermal penetration, whitening and barrier repair. Therefore, the composition can be applied to treat composite skin problems such as barrier damage and pigmentation, and has a good application prospect in the field of cosmetics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cosmetic technology, and more specifically, to a whitening and repairing composition containing a dual nanodelivery system and its preparation method. Background Technology

[0002] The stratum corneum (SC) of the skin consists of keratinocytes and a surrounding lipid bilayer. The main components of the lipid bilayer are ceramides (Cer, approximately 50 mol%), cholesterol (approximately 25 mol%), and free fatty acids (approximately 15 mol%). Natural stratum corneum lipids form two phases: a long-period phase (LPP, d≈13.4 nm) and a short-period phase (SPP, d≈6.4 nm). Among these, LPP, due to its highly ordered lipid molecular orientation, is the core structural basis for barrier function and hydration.

[0003] When the structure of the LPP phase decreases significantly or its molecular arrangement becomes disordered due to endogenous factors (such as aging, atopic constitution) or exogenous factors (such as excessive cleansing, improperly formulated lipid supplementation), it will directly lead to a sharp increase in transepidermal water loss (TEWL), a breakdown in the skin's water-locking ability, and easier penetration of external irritants, inducing and aggravating local micro-inflammatory reactions. In pathological states such as post-inflammatory hyperpigmentation (PIH), the release of inflammatory factors accompanying LPP damage will further activate melanocytes and cause disordered melanin metabolism and exfoliation in the epidermis, ultimately forming a malignant cascade of barrier defects, inflammation activation, and pigment deposition, resulting in a complex sub-healthy state of skin with dryness, sensitivity, redness, and stubborn pigmentation.

[0004] Currently, in the repair solutions for the stratum corneum, ceramide compositions are difficult to form a high proportion of LPP phase, resulting in short-lasting barrier repair and limited improvement after a single application of TEWL. Moreover, these products contain only a single active ingredient, which cannot address the complex skin problems of barrier damage and pigmentation. They also have low transdermal penetration and require high concentrations to be effective, further increasing the risk of irritation.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide a whitening and repairing composition containing a dual nano-delivery system and its preparation method. This whitening and repairing composition forms a high proportion of LPP phase, prolongs the barrier repair time, improves the transdermal penetration effect, effectively improves TEWL loss, and achieves the dual effects of whitening and repairing.

[0007] This invention is implemented as follows: On one hand, the present invention provides a whitening and repairing composition containing a dual nanodelivery system, comprising: a first nanodelivery system containing glycyrrhizin and a carrier material loaded with glycyrrhizin; and a second nanodelivery system containing a ceramide composition and a lipid component; The carrier materials include: poloxamer 407, phospholipids and antioxidants; the lipid components include: cholesterol or sterols, squalane, poloxamer 407 and phospholipids.

[0008] On the other hand, the present invention provides a method for preparing the above-mentioned whitening and repairing composition, which includes: mixing the first nanodelivery system and the second nanodelivery system in proportion to obtain the whitening and repairing composition; wherein, the second nanodelivery system is prepared by a three-stage temperature-controlled long-period phase induction method after the initial emulsion obtained by mixing and emulsifying the oil phase and the water phase. The temperature of the emulsion is 75~80℃; the three-stage temperature-controlled long-period phase induction method is divided into three stages: the first stage is: 0.5℃ / min to 65℃ and hold for 10 min; the second stage is: 0.3℃ / min to 45℃ and hold for 25~35 min; the third stage is: 0.5℃ / min to 30℃.

[0009] The present invention has the following beneficial effects: This invention, through the design of a specific ratio of ceramide composition and lipid components, combined with a three-stage temperature-controlled long-period phase induction process, prepares multilayer vesicles containing a high proportion of long-period phase. These vesicles can fuse and deliver with the stratum corneum lipid membrane, facilitating the transdermal penetration of poorly soluble and permeable EO-type ceramides. When these nanovesicles are combined with a carrier loaded with glycyrrhizin, the resulting composition exhibits significant synergistic effects in terms of glycyrrhizin stability, transdermal penetration, whitening, and barrier repair. Therefore, the composition of this invention can be applied to treat complex skin problems such as barrier damage and pigmentation, and has promising applications in the cosmetic field. Detailed Implementation

[0010] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0011] Damaged skin barrier is characterized by a decrease in the number and imbalance of intercellular lipids in the stratum corneum, as well as disruption of their cyclical structure. This exacerbates the invasion of irritants, leading to skin sensitivity, or accelerates the loss of body moisture, causing dry skin. Currently, supplementing the skin with appropriate types and proportions of physiological lipids (such as ceramides, cholesterol, and free fatty acids) has become a major direction for cosmetic products to address barrier damage. However, even with exogenous supplementation by mimicking the main components of intercellular lipids, the molecular weight (MW) of EO-type ceramides (690-712 Da) exceeds the transdermal penetration window, and their water solubility is <10. -8 The concentration of LPP in the product obtained by the known preparation process is ≤30%, making it difficult to form a high proportion of LPP phase; the transdermal permeability is poor, the duration of barrier repair is short, and the improvement effect of a single TEWL application is limited; it also cannot improve the melanin metabolism disorder caused by barrier damage.

[0012] To address the above problems, this invention proposes a whitening and repairing composition containing a ceramide composition and glycyrrhizin, employing a dual nanocarrier system. The dual nanocarrier system comprises a first nanodelivery system (also referred to as carrier D) and a second nanodelivery system (also referred to as carrier E).

[0013] Carrier D is composed of glycyrrhizin and a carrier material loaded with glycyrrhizin. Carrier D was designed in this invention because glycyrrhizin has a highly efficient competitive inhibitory effect on tyrosinase and is one of the commonly used skin-whitening raw materials. To address the problem that current barrier repair products cannot simultaneously improve melanin metabolism disorders caused by barrier damage, this invention combines it with a nanocarrier containing a ceramide composition. However, due to its poor water solubility and sensitivity to light / heat / oxidation, the conventionally solubilized nano-dispersion has a large particle size (>200 nm), poor stability, and insufficient permeability. Therefore, this invention uses glycyrrhizin as the core, combined with a specific carrier material to prepare carrier D.

[0014] The carrier materials include poloxamer 407, phospholipids, and antioxidants. In carrier D, phospholipids, due to their amphiphilic nature, can encapsulate glycyrrhizin in a hydrophobic core, improving its water solubility and ensuring its stability. Furthermore, phospholipids are a major component of biological membranes and have a natural affinity for the stratum corneum of the skin. The nanocarriers formed by phospholipids can fuse with the stratum corneum, forming lipid channels that help glycyrrhizin cross the barrier. Simultaneously, these nanoparticles can remain in the skin and continuously release glycyrrhizin, prolonging its duration of action. The addition of antioxidants is because glycyrrhizin is easily degraded by various environmental factors; antioxidants can improve its stability. Poloxamer 407 acts as a stabilizer in carrier D, maintaining the structural stability of the nanocarrier.

[0015] In some embodiments, the antioxidant is selected from at least one of vitamin E, sodium metabisulfite, EDTA-2Na, and tea polyphenols; the phospholipid in carrier D includes at least one of hydrogenated lecithin and soybean lecithin.

[0016] Carrier E is composed of a ceramide composition and lipid components, including cholesterol or sterols, squalane, poloxamer 407, and phospholipids. Carrier E is a multilayered vesicle containing ≥55 mol% long-period phase, prepared using a specific process with the ceramide composition as its backbone and combined with the lipid components. The addition of cholesterol or sterols and phospholipids is to mimic the composition of intercellular lipids; squalane replenishes skin lipids, aids in the repair of the damaged skin barrier, and reduces the penetration of external irritants.

[0017] In some embodiments, the ceramide composition comprises ceramide NP, ceramide AP, ceramide EOP, and ceramide EOS in a mass ratio of 10:2.5:1:1, at which the EO type is approximately 11.8 mol% (the necessary threshold for the formation of stable ≥10 mol% LPP).

[0018] In some embodiments, the phospholipids in carrier E include at least one of hydrogenated lecithin and soybean lecithin.

[0019] Compared to the approach of directly supplementing EO-type ceramides externally or relying on skin-assembled LPP, this invention uses exogenous "pre-made" LPP nanovesicles with pre-formed structures to directly fuse and deliver them to the stratum corneum lipid membrane. This breaks through the molecular weight / polarity bottleneck of EO-type ceramides (MW≈700Da, logP10~12), which not only helps solve the problem of transdermal penetration of EO-type ceramides and effectively utilizes the supplemented active ingredients, but also breaks free from the constraint of the 28-day stratum corneum renewal cycle, achieving a TEWL reduction of ≥25% in just 14 days.

[0020] The particle size of the carrier D loaded with glycyrrhizin prepared using the above-mentioned carrier material is 80~150 nm, and the PDI is ≤0.20; the particle size of the carrier E formed by the above-mentioned lipid components and ceramide is 30~200 nm.

[0021] In some embodiments, the mass ratio of carrier D to carrier E in the above composition is 7:3 to 9:1.

[0022] In this invention, after carrier D and carrier E are compounded in the above-mentioned proportion, the resulting composition exhibits a ≥92% retention rate of glycyrrhizin under accelerated conditions of 40℃ / 75% RH for 3 months, significantly improving the stability of glycyrrhizin. Moreover, compared to single active ingredients, the composition of this invention demonstrates significant synergistic effects in transdermal penetration, whitening, and barrier repair. Specifically, the cumulative penetration of glycyrrhizin over 24 hours is 3.2 to 8.3 times higher than that of free glycyrrhizin; the accumulation of ceramides in the stratum corneum is increased by more than 2.5 times; the TEWL decreases by 26.4% to 33.0% in 14-day human trials, and the B16 melanin inhibition rate is 53.8% to 70.4%. The TEWL repair rate of this invention is significantly higher than that of the scheme without glycyrrhizin, and the melanin inhibition rate is significantly higher than that of the scheme without ceramides.

[0023] In some embodiments, the whitening and repairing composition comprises, by weight percentage, the following components: 0.05%~0.5% glycyrrhizin, 0.1%~3.0% poloxamer 407, 0.3%~2.4% phospholipids, 0.15%~0.30% antioxidants, 0.5%~4.0% ceramide composition, 0.17%~1.33% cholesterol or sterols, 1.0%~3.5% squalane, and 2%~30% 1,3-butanediol.

[0024] In some embodiments, the antioxidant protectant consists of EDTA-2Na, sodium metabisulfite, and vitamin E, wherein the mass percentage of EDTA-2Na is 0.02%, the mass percentage of sodium metabisulfite is 0.05%, and the remainder is vitamin E.

[0025] To achieve the co-assembly of ceramide LPP vesicles and glycyrrhizin nanodispersion in the same continuous process and to increase the LPP ratio in carrier E, this invention also provides an optimized preparation method for the above-mentioned whitening and repairing composition, comprising: S1. Mix and melt ceramide, cholesterol or sterol, phospholipids and squalane to form a homogeneous, transparent oil phase; S2. Mix poloxamer 407, 1,3-butanediol and water to prepare a homogeneous aqueous phase; S3. Then the oil phase and the water phase are mixed and emulsified to obtain the primary emulsion; S4. The colostrum was subjected to three-stage temperature-controlled LPP induction to obtain a ceramide LPP vesicle dispersion (carrier E). S5. Under inert gas protection, glycyrrhizin was dissolved in an ethanol / 1,3-butanediol premixed system, and then poloxamer 407, phospholipids and antioxidants were added. After microfluidic homogenization, glycyrrhizin nano-dispersion (carrier D) was obtained. S6. After mixing carrier D and carrier E in a certain proportion, the above whitening and repairing composition is obtained.

[0026] In some embodiments, the temperatures for preparing the oil phase and the aqueous phase in S1 and S2 are both 75~80°C.

[0027] In some embodiments, the emulsification conditions in S3 are: shear emulsification at a rotation speed of 10000~15000 rpm / min for 5 min.

[0028] In some embodiments, the three-stage temperature-controlled long-period phase induction method in S4 is divided into three stages: the first stage is: decreasing the temperature at 0.5℃ / min to 65℃ and holding it at that temperature for 10 min; the second stage is: decreasing the temperature at 0.3℃ / min to 45~47℃ and holding it at that temperature for 25~35 min; and the third stage is: decreasing the temperature at 0.5℃ / min to 30℃.

[0029] In this invention, the inventors, by setting a specific ratio of ceramide composition (EO type > 10 mol%) and combining it with a three-stage temperature-controlled long-period phase induction method, oriented the ceramide composition and lipid molecules to form a long-period phase. SAXS characterization results show that the LPP molar ratio in the carrier E prepared by this invention is stable at 56 mol%~63 mol%, which is significantly higher than the LPP molar ratio in products prepared by existing processes, where LPP ≤ 30%.

[0030] In some embodiments, the conditions for microfluidic homogenization in S5 are: 600~1000 bar, 5 times.

[0031] In some embodiments, the mixing conditions for carrier D and carrier E in S6 are: low-speed mixing at 30°C for 15 minutes.

[0032] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0033] Example 1 This embodiment is a whitening and repairing composition containing a dual nano-delivery system, the components of which are as follows: glycyrrhizin 0.05wt%, ceramide NP 0.345wt%, ceramide AP 0.086wt%, ceramide EOP 0.034wt%, ceramide EOS 0.034wt%, β-sitosterol 0.17wt%, behenol 0.17wt%, HSPC phospholipids 0.30wt%, squalane 1.00wt%, poloxamer 407 3.00wt%, 1,3-butanediol 5.00wt%, antioxidant 0.15wt%, and deionized water to 100%.

[0034] The aforementioned antioxidant protectant is composed of EDTA-2Na, sodium metabisulfite, and vitamin E, wherein the amount of EDTA-2Na added is 0.02 wt%, the amount of sodium metabisulfite added is 0.05 wt%, and the amount of vitamin E added is 0.08 wt%.

[0035] The preparation method of the above whitening and repairing composition is as follows: 1. Oil phase preparation The ceramide composition, β-sitosterol, behenol, HSPC, and squalane were completely eutecticly dissolved at 75-80℃ to form a clear oil phase; 2. Aqueous phase preparation Mix 1,3-butanediol, poloxamer 407, and pure water thoroughly at 75-80℃; 3. High-shear emulsification Add the oil phase to the aqueous phase and emulsify at 12000 rpm for 5 min to obtain the primary emulsion; 4. Three-stage temperature-controlled LPP induction The obtained colostrum was cooled to 65℃ at 0.5℃ / min and held at that temperature for 10 min, then cooled to 45℃ at 0.3℃ / min and held at that temperature for 25 min, and finally cooled to 30℃ at 0.5℃ / min to obtain a ceramide LPP vesicle dispersion (carrier E). 5. Preparation of glycyrrhizin nanodispersion (carrier D) Glycyrrhiza glabra was dissolved in a 1,3-butanediol premixed system, and HSPC, poloxamer 407, and antioxidants were added. The mixture was then homogenized by microfluidic jet (800 bar × 5 times) under nitrogen protection throughout the process. 6. Mix carrier D and carrier E at a ratio of 9:1 (w / w) at 30°C at low speed for 15 min to obtain a dual nanocarrier composition.

[0036] The preparation methods of the whitening and repairing compositions in Examples 2-6 are the same as those in Example 1, except that the components are different and the temperatures induced by the three-stage temperature control LPP in the preparation steps are different, as shown in Table 1: Table 1. Components and key process parameters for Examples 1-6 (unit: wt%)

[0037] Table 1 verifies the particle size and PDI / LPP molar ratio of the compositions prepared in Examples 1-6. It can be seen that the LPP molar ratio is determined by the EO molar ratio (≈11.8 mol%) and the three-stage temperature control process, and is basically unrelated to the total concentration. In Examples 2-6, the LPP molar ratio tends to the 60 mol%~63 mol% plateau. Only in Example 1 (total Cer 0.50%) is the LPP slightly lower (56 mol%) due to the extremely low lipid concentration and the decrease in molecular collision frequency during the S4 isothermal stage, resulting in incomplete nucleation, but it is still ≥55%.

[0038] Comparative Example To verify the effectiveness of the components and processes in the examples, this experiment compared the effects of compositions prepared under different component additions and preparation parameters. A control group, CE1-CE13, was included in this experiment, and its differences from Example 3 are shown in Table 2. Table 2. Differences between control group CE1-CE13 and Example 3, and comparison of particle size effects.

[0039] Compared with Example 3, the amount of glycyrrhizin, poloxamer 407, and the isothermal temperature and time, as well as the ratio of ceramides in the three-stage temperature-controlled LPP induction step all affect the particle size and PDI of the final prepared composition.

[0040] To verify the influencing factors of the LPP molar ratio of the composition prepared in this invention, this experiment also compared the LPP molar ratios of CE7-CE11, and the results are shown in Table 3: Table 3 LPP molar ratio for CE7-CE11

[0041] As can be seen from the results in Table 3, the three-stage temperature-controlled LPP induction steps and the ceramide ratio both affect the LPP molar ratio.

[0042] Stability test This experiment compared the stability of Examples 1-6 with the control group CE1-CE13. The retention rate of glycyrrhizin was tested by liquid chromatography (40℃ / 75%RH, 3 months). The specific test method was as follows: HPLC quantification method for glycyrrhizin: C18 column (250×4.6mm, 5μm), mobile phase acetonitrile-0.1% phosphoric acid water 55:45, flow rate 1.0mL / min, column temperature 30°C, detection wavelength 282nm, injection 10μL. Sample was extracted with methanol by sonication for 30min, filtered through a 0.22μm filter membrane, and quantified by external standard method. Linearity: 0.5-50μg / mL (r 2 ≥0.9995), recovery rate 98-102%, RSD≤2%.

[0043] The test results are shown in Table 4: Table 4. Glycyrrhizin retention rate at 40℃ / 75%RH / 3 months

[0044] As can be seen from the results in Table 4, the carrier has a significant impact on the stability of glycyrrhizin. In addition, the proportion of ceramide also affects the retention rate of glycyrrhizin to varying degrees.

[0045] Cellular melanin inhibition test The melanin inhibition effect of this experiment compared the control group with that of the example. The specific test method is as follows: B16-F10 cells were used at a rate of 1×10 5 / wells were inoculated into 6-well plates. After 24 hours of adhesion, complete medium containing 50 μmol / L glycyrrhizin (inducible with 100 nmol / L α-MSH) was added, and the culture was allowed to incubate for 72 hours. After washing with PBS, the culture was lysed in 1 mol / L NaOH (containing 10% DMSO) at 80°C for 1 hour, and the absorbance was measured at 405 nm. Protein was normalized using the BCA method, and the inhibition rate was calculated as (1 - A sample / A model) × 100%. Free glycyrrhizin was contained in a 0.25 wt% butanediol solution. The experimental results are shown in Table 5. Table 5 Comparison of melanin content inhibition rates in B16-F10 melanoma cells

[0046] The above differences were analyzed by one-way ANOVA + Dunnett's post-hoc method, with P < 0.01 relative to the free glycyrrhizin group. Cell viability in all groups was >90%, with no significant cytotoxicity. The melanin inhibition rates at 50 μmol / L in Examples 3 and 6 were 61.5% and 70.4%, respectively. The melanin inhibition rates at 50 μmol / L for free glycyrrhizin, CE1, and CE2 were 50.6%, 8.5%, and 44.6%, respectively. The B16 inhibition rate in Example E3 was significantly higher than that in CE2 (without ceramide), indicating that the ceramide-LPP bilayer facilitates glycyrrhizin entry into cells and prolongs its retention, thereby synergistically enhancing the melanin inhibition effect.

[0047] 3D Skin Melanin Content Inhibition Rate Test This experiment compared the inhibition rate of 3D skin melanin content in the embodiment and the control group. The specific test method is as follows: After the 3D humanized pigmented reconstructed epidermal model MelanoDermMEL-300-B tissues arrived, they were pre-equilibrated for 24 hours in EPI-100-NMM-113 gas-liquid interface medium. The medium was changed daily, and 5 μL of the test sample was applied topically to the tissue surface for 14 consecutive days. Tissues were harvested on days 0, 7, and 14, washed with PBS, and the surface L* value was directly measured using a portable colorimeter (KonicaMinoltaCM-700d, D65 / 10°). The average value was taken from three points for each tissue, n=4. The experimental results are shown in Table 6. Table 6. Changes in L* values ​​after 14 days of continuous administration of MatTek MEL-300-B (n=4 tissues, mean±SD)

[0048] As can be seen from Table 6, the ΔL* of Examples 3 and 6 on day 14 were +4.3 and +5.0, respectively, and the melanin content reduction rate reached 42.5% and 48.7%, respectively. The effect was significantly better than 2% nicotinamide, 2% α-arbutin and free glycyrrhizin (P<0.01).

[0049] Transdermal absorption rate test The transdermal absorption rate of this experimental comparison example and the control group was specifically tested using the following method: Franz diffusion cell method for ex vivo porcine skin: Ear skin from 8-month-old miniature pigs was cut to a depth of 500 μm and placed in a Franz cell (0.64 cm²), with the stratum corneum facing upwards and the dermis immersed in receiving solution (PBS pH 7.4 + 30% ethanol, magnetically stirred at 500 rpm) at 32 ± 0.5 ℃. 10 μL / cm² of sample was loaded, and the cell was semi-open. 500 μL of sample was collected every 24 hours and replenished immediately. HPLC quantification was performed. At the endpoint, the stratum corneum deposition was measured by continuous peeling with tape 20 times. The epidermis and dermis were then separated by heat at 60℃ for homogenization and extraction, all in the dark. The test results are shown in Table 7. Table 7. Results of Franz diffusion cell percutaneous osmosis test

[0050] Example 3 showed a 3.2-fold increase in cumulative penetration compared to the free light glycyrrhizin group; Example 6 showed an 8.3-fold increase compared to the free light glycyrrhizin group; due to LPP deficiency, the ceramide stratum corneum accumulation of CE7 was only 3.4 μg·cm³. -2 The above results indicate that the three-stage temperature-controlled process for LPP formation is positively correlated with transdermal absorption.

[0051] Transdermal water loss test This experiment compared transdermal water loss (TEWL) between the experimental and control groups. The specific testing method was as follows: Subjects were placed in a constant humidity environment (20-22℃, 40%-60% relative humidity) for 20-30 minutes to equilibrate. The inner forearm or cheek was selected as the test site. The skin in the test area was cleaned, and surface oils and cosmetic residues were removed. The probe of the TEWL measuring instrument was gently placed vertically on the skin surface, ensuring close contact without applying additional pressure. Measurements were repeated 2-3 times at each test site, and the arithmetic mean was taken. The unit of measurement was g·m³. -2 ·h -1 The amount of moisture loss. The TEWL test results are shown in Table 8: Table 8 TEWL Test Results

[0052] Note: *CE1 has a very small p-value because the 5 volunteers all shifted in the same direction, but its absolute decrease is less than 0.3 g·m⁻¹.-2 ·h -1 (This has no biological significance; it indicates that glycyrrhizin itself has no repair effect on the barrier, and the improvement of TEWL comes from the ceramide LPP system.)

[0053] Table 8 shows that the composition of Example 3 reduced TEWL by 25.6% after 14 days (P<0.001, n=5), which was significantly better than CE2 (without ceramide, only a 0.9% reduction) and CE7 (without three-stage temperature control, a 10.5% reduction), indicating that EO-type ceramide + three-stage temperature-controlled LPP induction is the main factor for barrier repair. Moreover, compared with CE1, the TEWL repair rate of Example 3 was significantly higher than that of CE1, suggesting that glycyrrhizin indirectly promotes barrier repair by inhibiting IL-1α / NF-κB, thereby synergistically improving the TEWL repair effect.

[0054] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A whitening and repairing composition containing a dual nanodelivery system, characterized in that, include: The first nanodelivery system includes glycyrrhizin and a carrier material loaded with glycyrrhizin; A second nanodelivery system comprising a ceramide composition and a lipid component; The carrier material includes: poloxamer 407, phospholipids and antioxidants; the lipid components include: cholesterol or sterols, squalane, poloxamer 407 and phospholipids.

2. The whitening and repairing composition according to claim 1, characterized in that, The ceramide composition comprises ceramide NP, ceramide AP, ceramide EOP, and ceramide EOS in a mass ratio of 10:2.5:1:

1.

3. The whitening and repairing composition according to claim 2, characterized in that, The second nanodelivery system is a multilayer vesicle with a long periodic phase formed by combining the ceramide composition as a framework with the lipid component; The particle size of the second nanodelivery system is 30~200 nm, and the molar ratio of the long-period phase is ≥55 mol.

4. The whitening and repairing composition according to claim 1, characterized in that, The antioxidant is selected from at least one of EDTA-2Na, sodium metabisulfite, and vitamin E; the phospholipid includes at least one of hydrogenated lecithin and soybean lecithin.

5. The whitening and repairing composition according to claim 4, characterized in that, The particle size of the first nanodelivery system is 80~150 nm, and the PDI is ≤0.

20.

6. The whitening and repairing composition according to claim 1, characterized in that, The mass ratio of the first nanodelivery system to the second nanodelivery system is 7:3 to 9:

1.

7. The whitening and repairing composition according to claim 6, characterized in that, The whitening and repairing composition contains the following components by weight percentage: 0.05%~0.5% glycyrrhizin, 0.1%~3.0% poloxamer 407, 0.3%~2.4% phospholipids, 0.15%~0.3% antioxidants, 0.5%~4.0% ceramide composition, 0.17%~1.33% cholesterol or sterols, 1.0%~3.5% squalane, 2%~30% 1,3-butanediol.

8. A method for preparing the whitening and repairing composition according to any one of claims 1 to 7, characterized in that, include: The whitening and repairing composition is obtained by mixing the first nanodelivery system and the second nanodelivery system in a certain proportion. The second nanodelivery system is prepared by a three-stage temperature-controlled long-period phase induction method using a primary emulsion obtained by mixing and emulsifying oil and water phases. The temperature of the emulsion is 75~80℃; The three-stage temperature-controlled long-period phase induction method consists of three stages: the first stage is: decreasing the temperature at 0.5℃ / min to 65℃ and holding it at that temperature for 10 min; the second stage is: decreasing the temperature at 0.3℃ / min to 45~47℃ and holding it at that temperature for 25~35 min; and the third stage is: decreasing the temperature at 0.5℃ / min to 30℃.

9. The preparation method according to claim 8, characterized in that, The method for preparing the colostrum includes: Ceramides, cholesterol or sterols, phospholipids and squalane are mixed and melted to form a homogeneous, transparent oil phase; poloxamer 407, 1,3-butanediol and water are mixed to prepare a homogeneous aqueous phase; then the oil phase and aqueous phase are mixed and emulsified to obtain the primary emulsion. The temperatures of the oil and water phases are 75~80℃; The emulsification conditions are: shear emulsification at a rotation speed of 10000~15000 rpm / min for 5 min.

10. The preparation method according to claim 8, characterized in that, The method for preparing the first nanodelivery system includes: Under inert gas protection, glycyrrhizin was dissolved in a 1,3-butanediol premixed system, and then poloxamer 407, phospholipids and antioxidants were added. After microfluidic homogenization, the first nanodelivery system was obtained. The conditions for homogenizing the microjets are: 600~1000 bar × 5 times.